Identifikasi Morfologi Haematopinus sp. Pada Sapi Limousin Asal Karanganyar dan Sapi Fries Holland (FH) Asal Boyolali - Aan Awaludin; Yudhi Ratna; Kurniasih Kurniasih (Politeknik Negeri Jember, 2017)
Ectoparasitic infestation is one of the major animal health issues affecting on the livestock industry in many parts of the world. Haematopinus sp. is an ectoparasite that causes pediculosis (ptiriasis) in cattle, investing in large quantities causes itching and weight loss because it causes irritation, discomfort, and several studies explain that Haematopinus sp. can lead to decreased milk production and decreased quality of cow products. The objective of the study was to identify Haematopinus sp. in Limousin cows from Karanganyar and Fries Holland (FH) cows from Boyolali based on their morphology. Haematopinus sp. samples were taken from the tail end area, perineal vulva, ears and around the eyes of cows as much 5 – 10 tails of each 1 cow that was invested. The results of morphological identification were analyzed descriptively. Haematopinus sp. samples in Limousin cows from Karanganyar and Fries Holland (FH) cows from Boyolali was identified as Haematopinus quadripertusus. Keywords : Ectoparasit, Haematopinus, Louse, Ptiriasis